2005
DOI: 10.1158/1535-7163.mct-05-0027
|View full text |Cite
|
Sign up to set email alerts
|

Pristimerin induces caspase-dependent apoptosis in MDA-MB-231 cells via direct effects on mitochondria

Abstract: Pristimerin, a naturally occurring triterpenoid, has been shown to cause cytotoxicity in several cancer cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
91
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 40 publications
8
91
0
Order By: Relevance
“…Furthermore, we found that treatment with pristimerin inhibited the migration and invasion of MDA-MB-231 cells in vitro in a dose-dependent manner and the growth and invasion of implanted breast tumors in vivo. These novel data extend previous findings (Wu et al, 2005;Yang et al, 2008;Tiedemann et al, 2009) and suggest that pristimerin may have broad antitumor activity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, we found that treatment with pristimerin inhibited the migration and invasion of MDA-MB-231 cells in vitro in a dose-dependent manner and the growth and invasion of implanted breast tumors in vivo. These novel data extend previous findings (Wu et al, 2005;Yang et al, 2008;Tiedemann et al, 2009) and suggest that pristimerin may have broad antitumor activity.…”
Section: Discussionsupporting
confidence: 90%
“…Ideally, simultaneous 1 can inhibit tumor cell proliferation by inhibiting the NF-κB pathway and cell cycling (Boire et al, 2005;Costa et al, 2008;Yang et al, 2008;Byun et al, 2009;Tiedemann et al, 2009). In addition, prestimerin has been reported to induce caspase-dependent apoptosis of breast cancer cells (Wu et al, 2005) and prostate cancer cells in vitro (Yang et al, 2008). Recently, pristimerin is reported to be a potent natural triterpenoid inhibitor of 20s proteasome chymotrypsin-like activity in prostate cancer cells (Tiedemann et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence indicates that mitochondria play a pivotal role in the apoptotic process in mammalian cells (22)(23)(24). Disruption of mitochondrial ∆Ψm is considered to be an indicator of mitochondria damage and is generally defined as an early stage of apoptosis, preceding efflux of small molecules from the mitochondria (including cytochrome c, apoptosis-inducing factor) and followed by caspase-9/-3 cascade activation (25)(26)(27)(28). In the present study, we found the marked decrease of pro-caspases (pro-caspase-3 and -9) by 7-PEC after the breakdown of ∆Ψm, suggesting that the mitochondria-mediated pathway is involved in 7-PEC-triggered apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that pristimerin has promising clinical potential as both a therapeutic and chemopreventive agent for various types of cancer such as pancreatic cancer, glioma, leukemia, cervical cancer, prostate cancer and breast cancer (6)(7)(8)(9)(10)(11). Pristimerin has been shown to induce cell death via a number of several mechanisms, including proteosome inhibition, caspase activation, inhibition of cell cycle progression, and suppression of antiapoptotic nuclear factor kappa B (NF-κB) and Akt signaling pathways (6,9).…”
Section: Introductionmentioning
confidence: 99%
“…Pristimerin has been shown to induce cell death via a number of several mechanisms, including proteosome inhibition, caspase activation, inhibition of cell cycle progression, and suppression of antiapoptotic nuclear factor kappa B (NF-κB) and Akt signaling pathways (6,9). In breast cancer, it has been reported that pristimeirin induces apoptotic cell death in MDA-MB-231 breast cancer cells in a caspase-dependent manner (11). In addition, prestimerin has been demonstrated to inhibit the migration and invasion of breast cancer cells (12).…”
Section: Introductionmentioning
confidence: 99%